Collaborative postgraduate training in family medicine and primary care: Reflections on my visit to South Africa - Felicity Goodyear-Smith (AOSIS, 2018)
This reflection describes my funded visit to South Africa to assist in primary care research capacity building as Chair, WONCA Working Party on Research (WP-R). The trip included time at the Universities of Walter Sisulu, Limpopo and Stellenbosch to mentor postgraduate students working on master's and PhD theses. I held one-on-one and group sessions and ran interactive scientific writing workshops. I assisted with the establishment of a Stellenbosch University Family Physician Research Network of faculty academics and family physicians (FP) which will generate research questions from community stakeholders. I also ran a writing workshop at the Joint 5th WONCA Africa and 20th South African National Family Practitioners Conference in Pretoria attended by about 100 conference delegates, ranging from FP registrars to academics with PhDs and peer-reviewed publications. A WP-R panel presentation of international comparisons of primary care systems was also held at this conference, with the countries of Ghana, Malawi, Zimbabwe, Ethiopia and Nigeria presented. During my stay, Ireflected on the differences between family medicine in South Africa and in my home country, New Zealand (NZ). In South Africa, there is high prevalence of HIV and tuberculosis, seldom seen in NZ. Donor-funded vertical programmes cause significant fragmentation of care. Family doctors generally work in district hospitals, providing consultancy support to nurseled clinics. They have a laudable requirement to complete a Master's in Medicine in conjunction with vocational training. Academic family medicine in South Africa is coming of age. I feel privileged to play a small part in its journey to maturity.